Performance Analysis of Extraction Condensing Turbine - Unit 1 at Pltu X, Bekasi, West Java - Komarudin, Komarudin; Abrianto, H. Heru; Multi, Abdul; Putra Utama, Adi (International Journal of Advanced Multidisciplinary, 2023)
In 2014, Cikarang Listrindo Energy built a steam power plant in Babelan to participate in the government programs. In April 2017, Unit 1 of PLTU Babelan has been operated. After the plant has been in operation for 4 months, the plant will have a performance test for the main part of the steam power plant, one of which is the steam turbine performance test. This performance test purpose is to get actual performance data where it will be compared to the design data, and it willl be used for warranty from the steam turbine contractor. The performance test is using ASME PTC 6 for steam turbine performance test. The steam turbine performance test can be seen from several parameters such as test capability, heat rate and turbine efficiency. The results of the steam turbine performance test based on the design are: the output power is 138,010 MW; the heat rate is 8865 kJ/kWh; and the turbine efficiency is 87.38%. Meanwhile the results of the performance test based on commissioning are: the output power is 139,295 M; the heat rate is 8919 kJ/kWh; and the turbine efficiency is 87.03%. The actual performance test results are: the output power is 137,595 MW, the heat rate is 8830.64 kJ/kWh, and the turbine efficiency is 88.65%. The tolerance given from ASME PTC 6 is 2%. Exhaust turbine pressure affect the turbine efficiency, where as lower exhaust turbine pressure causes higher turbine efficiency.